Refugee integration: A worthwile investment - Stefan Bach; Herbert Brücker; Peter Haan; Agnese Romiti; Kristina van Deuverden; Enzo Weber (DIW Economic Bulletin, 2017)
The initial fiscal costs associated with refugee integration are quite high-but as more and more refugees join the labor force, a reduction in ongoing welfare costs and an increase in government revenue will result. Against this background, the Institute for Employment Research (IAB) in Nuremberg and DIW Berlin conducted a joint investigation (funded by the German Federal Ministry of Labor and Social Affairs) into the overall economic and fiscal impacts of investing in the labor market integration of the refugees who arrived in Germany in 2015. The results show that investing in refugees' language skills and educational qualifications promises high returns.
Keywords: F22; I21; H52; 330; refugees; migration; labor market integration; budget impact